2013
DOI: 10.1287/isre.1120.0455
|View full text |Cite
|
Sign up to set email alerts
|

When Social Media Can Be Bad for You: Community Feedback Stifles Consumer Creativity and Reduces Satisfaction with Self-Designed Products

Abstract: Enabling consumers to self-design unique products that match their idiosyncratic preferences is the key value driver of modern mass customization systems. These systems are increasingly becoming “social,” allowing for consumer-to-consumer interactions such as commenting on each other's self-designed products. The present research examines how receiving others' feedback on initial product configurations affects consumers' ultimate product designs and their satisfaction with these self-designed products. Evidenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
97
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 110 publications
(100 citation statements)
references
References 70 publications
3
97
0
Order By: Relevance
“…In practice, platforms for open idea sourcing tend to be highly interactive to spur communication and collaboration among participants. While this was a deliberate decision based on prior work (Hildebrand et al 2013 Information Systems Research 27(1), pp. 27-48, © 2016 INFORMS it may lead to a slight deviation from real world-based settings, in which users may also provide qualitative feedback, i.e., comments that may dynamically change ideas.…”
Section: Limitations and Future Researchmentioning
confidence: 99%
“…In practice, platforms for open idea sourcing tend to be highly interactive to spur communication and collaboration among participants. While this was a deliberate decision based on prior work (Hildebrand et al 2013 Information Systems Research 27(1), pp. 27-48, © 2016 INFORMS it may lead to a slight deviation from real world-based settings, in which users may also provide qualitative feedback, i.e., comments that may dynamically change ideas.…”
Section: Limitations and Future Researchmentioning
confidence: 99%
“…Recent findings from an online co-creating study can provide some explanation [13]. These findings showed that feedback may lower the uniqueness of ideas as ideas shift after refinement from their extreme position towards the mainstream.…”
Section: Resultsmentioning
confidence: 93%
“…Feedback describes information intended to "confirm, add to, overwrite, tune, or restructure information in memory, whether that information is domain knowledge, meta-cognitive knowledge, beliefs about self and task, or cognitive tactics and strategies" [20, p. 5740]. Past studies investigated different types of feedback, such as social feedback [15], community feedback [13], directed feedback, random feedback [14], corrective feedback [21], cognitive feedback [22], and process feedback [23], and their effects on performance outcomes such as idea quality [12] or affective outcomes such as satisfaction [13].…”
Section: Feedback Intervention Theory and Hypotheses Developmentmentioning
confidence: 99%
See 2 more Smart Citations